Instream Large Wood: Denitrification Hotspots with Low N2O Production1. (June 2014) - Lazar, Julia G.; Gold, Arthur J.; Addy, Kelly; Mayer, Paul M.; Forshay, Kenneth J.; Groffman, Peter M.
Abstract We examined the effect of instream large wood on denitrification capacity in two contrasting, lower order streams — one that drains an agricultural watershed with no riparian forest and minimal stores of instream large wood and another that drains a forested watershed with an extensive riparian forest and abundant instream large wood. We incubated two types of wood substrates (fresh wood blocks and extant streambed wood) and an artificial stone substrate for nine weeks in each stream. After in situ incubation, we collected the substrates and their attached biofilms and established laboratory‐based mesocosm assays with stream water amended with 15N‐labeled nitrate‐N. Wood substrates at the forested site had significantly higher denitrification than wood substrates from the agricultural site and artificial stone substrates from either site. Nitrate‐N removal rates were markedly higher on woody substrates compared to artificial stones at both sites. Nitrate‐N removal rates were significantly correlated with biofilm biomass. Denitrification capacity accounted for only a portion of nitrate‐N removal observed within the mesocosms in both the wood controls and instream substrates. N2 accounted for 99.7% of total denitrification. Restoration practices that generate large wood in streams should be encouraged for N removal and do not appear to generate high risks of instream N2O generation.